Elevated Pentraxin 3 in Obese Adipose Tissue Promotes Adipogenic Differentiation by Activating Neuropeptide Y Signaling - Shin, Min-Kyung; Choi, Bongkun; Kim, Eun-Young; Park, Ji-Eun; Hwang, Eui Seung; Lee, Hyang Ju; Kim, Min Kyung; Kim, Ji-Eun; Kim, Seong Who; Chang, Eun-Ju (Frontiers in Immunology, 2018)
Obesity is accompanied by chronic systemic inflammation characterized by macrophage infiltration of obese tissues, an elevated plasma level of inflammatory substances, and excessive accumulation of lipids. The pro-inflammatory factor pentraxin 3 (PTX3) is also elevated in obese tissues, suggesting its potential role in adipogenesis. We found by analyzing murine preadipocyte 3T3-L1 cells, and human adipocytes derived from mesenchymal stem cells, that locally elevated PTX3 in obese adipose tissue augments adipocyte differentiation and subsequent lipid accumulation. This occurs via the upregulation of adipogenesis-related transcription factors. PTX3 enhanced lipid accumulation in murine 3T3-L1 cells by upregulating the expression of neuropeptide Y (NPY)/NPY receptor (NPYR) expression in preadipocytes. Pharmacological inhibition by NPYR antagonists abolished these effects. NPY also promoted the production of reactive oxygen species (ROS), a known trigger of adipogenesis. NPYR antagonists as well as antioxidant N-acetylcysteine showed anti-adipogenic effects by reducing the ROS levels, indicating that PTX3 mediates adipogenesis through NPY-dependent ROS production. These findings suggest that PTX3 plays a key role in the development of obesity by enhancing adipocyte differentiation and lipid synthesis via NPY/NPYR signaling. These observations provide a mechanistic explanation for the adipogenesis mediated by PTX3.